The Influence of Balanced Diet on Adolescent Nutritional Status - Faradina, Anggia (Journal Nutrizione, 2024)
This study aims to analyze the effect of a balanced diet on the nutritional status of adolescents through a qualitative approach with a literature study method. Adolescents are an age group that is vulnerable to nutritional disorders due to biological, psychological, and social changes that affect their eating habits. The results of the study show that a diet that includes balanced nutrition has a direct impact on nutritional status indicators such as Body Mass Index (BMI), hemoglobin levels, and the risk of obesity or anemia. Low nutritional knowledge and environmental influences such as family economy, culture, and school canteens also influence food choices. Nutrition education that is carried out continuously, both through social media and school curriculum, has been shown to increase awareness and behavior of healthy food consumption in adolescents. Thus, the implementation of adolescent nutrition intervention programs must consider a holistic approach that involves family, school, and community. The results of this study are expected to be a reference for formulating strategies to improve adolescent nutrition preventively and sustainably.